Pengaruh Servant Leadears Etos Kerja Islami dan Kompensasi terhadap Kinerja Karyawan dengan Organization Citizenship Behaviour (OCB) sebagai Variabel Intervening - Asroti Asroti; Mochlasin Mochlasin; Musalim Ridlo (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine the effect of servant leadership, Islamic work ethic and compensation on employee performance with organizational citizenship behavior as an intervening variable (Study on BMT in Semarang Regency). The type of research used in this thesis is quantitative research. The method of collecting data is through questionnaires distributed to managers at BMT Semarang Regency. Samples were taken as many as 100 respondents with puposive sampling technique. The obtained data is then processed using the SPSS version 22 tool. This analysis includes validity test, reliability test, statistical test, coefficient test determination, F test, T test, classical assumption test and path analysis test (path analysis). The results of the T test show that Servant Leadership, compensation has a positive and significant effect on employee performance, Islamic work ethic and Organizational citizenship behavior have a negative and insignificant effect on employee performance. Path analysis test shows that there is a mediating influence of servant leadership and Islamic work ethic on employee performance through Organization Citizenship Behavior, there is no mediating effect of compensation on employee performance through Organization Citizenship Behavior (OCB).